2018
DOI: 10.1093/jac/dky462
|View full text |Cite
|
Sign up to set email alerts
|

Combination treatment with the cap-dependent endonuclease inhibitor baloxavir marboxil and a neuraminidase inhibitor in a mouse model of influenza A virus infection

Abstract: ObjectivesBaloxavir marboxil (formerly S-033188) is a first-in-class, orally available, cap-dependent endonuclease inhibitor licensed in Japan and the USA for the treatment of influenza virus infection. We evaluated the efficacy of delayed oral treatment with baloxavir marboxil in combination with a neuraminidase inhibitor in a mouse model of lethal influenza virus infection.MethodsThe inhibitory potency of baloxavir acid (the active form of baloxavir marboxil) in combination with neuraminidase inhibitors was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 33 publications
5
66
0
Order By: Relevance
“…Using the Chou and Talalay method, a combination index was generated, and based on this experimental data the observed effect was classified as additive for each of the NAIs. These data complement a previously published study that showed that there is a synergistic effect on influenza A virus replication when baloxavir is used in combination with NAI (Fukao et al, 2019).…”
Section: Combination Effects Of Baloxavir Acid With Neuraminidase Inhsupporting
confidence: 90%
“…Using the Chou and Talalay method, a combination index was generated, and based on this experimental data the observed effect was classified as additive for each of the NAIs. These data complement a previously published study that showed that there is a synergistic effect on influenza A virus replication when baloxavir is used in combination with NAI (Fukao et al, 2019).…”
Section: Combination Effects Of Baloxavir Acid With Neuraminidase Inhsupporting
confidence: 90%
“…We previously reported the antiviral activities of BXA in vitro and in a mouse model. 9,[29][30][31] Interestingly, the half-life of BXA in ferrets was significantly shorter than in humans, Figure S4). Although high levels of BXM were detected in ferrets in contrast to humans and mice, its CEN inhibitory activity was ≥200-fold lower than that of BXA in in vitro studies, which indicates that the plasma concentration of BXA is more crucial for determining the dosing regimen of BXM.…”
Section: Discussionmentioning
confidence: 98%
“…For A(H3N2) infections, concentrations of 0.39–200 nmol/L were used for BXA; 7.8–4000 nmol/L for oseltamivir; 35.15–16,000 nmol/L for zanamivir; 1.56–800 nmol/L for peramivir; 312.5–160,000 nmol/L for favipiravir; 78.125–40,000 nmol/L for ribavirin, diluted in MEM and TPCK trypsin (1 mg/mL). These dilutions were based on Fukao et al [ 26 ] and on our preliminary experiments. Forty-eight hours later, cell viability was assessed by adding 10 µL/well of 3-(4,5-dimethylthiazol-2yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium, inner salt (MTS) (Cell Titer 96 Aqueous One Solution Cell Proliferation Assay, Promega, Madison, WI, USA) and absorbance was measured at 490 nm with a plate reader.…”
Section: Methodsmentioning
confidence: 99%
“…Several in vitro and in vivo studies have shown that dual antiviral therapies may have a significant positive effect on the treatment of influenza infections [ 13 , 23 , 24 , 25 ] and could further delay the emergence of resistance. Indeed, combination therapy with BXM and oseltamivir was reported to produce synergistic responses against the influenza A/PR/8/34 strain and to reduce virus titers [ 26 ]. However, there is a lack of information about combination therapy between this new polymerase inhibitor and other approved drugs.…”
Section: Introductionmentioning
confidence: 99%